THE ROLE OF FORENSIC MEDICINE IN THE CRIMINAL EVIDENCE PROCESS - Setyo Trisnadi (Jurnal Pembaharuan Hukum, 2021)
Forensic Medicine has a very important role in disclosing a crime that has occurred, especially for cases that are difficult to solve or require special techniques to disclose. Its also very helpful for law enforcement officers to reveal a criminal act that occurs from the level of investigation to the stage of court against cases related to the human body or soul so as to make light of a criminal act that occurred. In cases related to injuries, health and life of a person caused by a crime, the doctor can explain as an expert witness in the settlement of criminal cases. In this study using a normative juridical method. The results obtained stated that the role of forensics in the examination of the judicial process was intended to determine the presence or absence of persecution, to determine whether or not there was a crime or a violation of decency, to determine the age of a person, to determine the certainty of a baby who died in the womb of a mother and examination at the scene. Cases are usually requested by the authorities, in the event that someone is found dead.